Efecto de extractos botánicos a base de ají (Capsicum frutescens) y nenn (Azasirachta indica) sobre el caracol manzana (pomacea canaliculata). - Bajaña Pérez, Darwin Javier (2016)
Considering the various problems involving the uncontrolled use of pesticides in modern agriculture is conducted this investigation in order to assess the effect of the preparations of pepper and neem on the apple snail (Pomacea canaliculata). To do snails were collected in rice fields and took to the microbiology laboratory of Campus Manuel Alvarez Make UTEQ, where they were fed and applied the treatments under study, then carry out the measurement of the variables. Design completely randomized was used with six treatments in four replications. The best results in terms of mortality, reduced feed intake and egg masses were obtained with metaldehyde, however with botanical extracts of neem and chili dose of 175 cc / l and 150 cc / l, respectively mortality rates were obtained acceptable (50 to 70% in your order) and a significant decrease in feed intake (64 and 61%) and oviposition (71.4% and 85.7%), representing an organic method of apple snail control, meeting the demands from a Organic farming, for application in various crops threatened by this scourge. Keywords: apple snail, bio-insecticides, neem, pepper.